Buprenorphine Outpatient Outcomes Project: can Suboxone be a viable outpatient option for heroin addiction? - Charmian D. Sittambalam; Radhika Vij; Robert P. Ferguson (Journal of Community Hospital Internal Medicine Perspectives, 2014)
Background: Opioid dependence treatment traditionally involves methadone clinics, for which dispensing schedules can be cumbersome. Buprenorphine, a partial agonist of the mu receptor and antagonist of the kappa receptor, is a potential outpatient alternative to methadone. Funded by a grant from the State of Maryland's Community Health Resources Commission (CHRC), the Buprenorphine Outpatient Outcomes Project (BOOP) evaluates the outcome of Suboxone (buprenorphine/naloxone) treatment on abstinence from heroin use, rates of emergency room visits and hospitalizations, legal issues, and quality of life. Methods: Active heroin users were recruited between June 2007 and June 2010 and induction therapy with Suboxone was instituted during hospitalization. Once discharged, patients were followed as outpatients for maintenance treatment and counseling. Data were collected from electronic medical records, Maryland state legal records, and SF-36® Health Surveys regarding several parameters and patients were categorized according to duration of treatment with Suboxone into one of three groups: <1 month, 1–3 months, and >3 months. Results: A total of 220 participants were included in the study. The age range of participants was 18–67 years with most being African American males. Eighty-three (38%) remained in the study for at least 1 month, with 37 of the 83 (45%) remaining in treatment for >3 months. Ten of the 37 (27%) never relapsed after their longest period of abstinence from heroin. During the first year after initiating treatment with Suboxone, hospitalization and emergency room visit rates for all 220 participants decreased by 45 and 23%, respectively, as compared to the year prior to starting treatment. The number of legal charges for drug possession decreased from 70 to 62. Anecdotally, the quality of life seemed to improve in those who were treated with Suboxone for longer periods of time and received regular counseling. Conclusion: Overall, Suboxone is an effective treatment method for heroin addiction and is a viable outpatient therapy option. Individualized treatment plans and counseling must be implemented for maximum benefits to be seen. Retention of patients for a long duration of therapy was difficult, but for those who did remain, benefits were seen in overall health, abstinence from heroin use, cognition, and quality of life.